Greenhouse Gas Emissions from Peat Soils Cultivated to Rice Field, Oil Palm and Vegetable - Hadi, Abdul; Affandi, Dedi Nursyamsi; Bakar, Rosenani Abu; Inubushi, Kazuyuki (UNIVERSITY OF LAMPUNG, 2012)
Presently, about 20% of oil palm (Elaeis guineensis Jacq) fields in Indonesia are on peat soil, in addition to that otherarea of peat soil has been conventionally used for rice field and vegetables. To elucidate the global warmingpotentials of peat soils cultivated to oil palm, vegetable or rice field, field experiment has been carried out in SouthKalimantan. Air samples were taken from rice field, oil palm and vegetable fields in weekly basis for six month periodand analyzed for concentrations of N2O, CH4 and CO2. The global warming potentials (GWP) of the three gases werecalculated by multiplying the emission of each gas with their respective mole warming potential. This step wasfollowed by the addition of the three gases’ GWP to have the total GWP. The results showed that the emissions ofgreenhouse gases from peat soils changed seasonally and varied with the crops cultivated. Oil palm has resultedthe highest GWP, mostly contributed by N2O. There was no statistical different in total GWP of paddy andvegetable fields. The annual N2O emission from oil palm field was 4,582 g N ha-1 yr-1. Water, nutrients and organicmatter managements are among the potential techniques to minimize gas emissions from oil palm field which needfield trials.